2017
DOI: 10.1177/0022034517728496
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of 12% and 38% Silver Diamine Fluoride Treatment

Abstract: This 30-mo randomized clinical trial compared the effectiveness of 2 concentrations (12% or 38%) of silver diamine fluoride (SDF) and 2 periodicity of application (once or twice a year) in arresting cavitated dentin caries in primary teeth. Children aged 3 to 4 y who had at least 1 active cavitated caries lesion were enrolled and randomly allocated into 4 groups for intervention. Group 1 had 12% SDF applied annually (every 12 mo), group 2 had 12% SDF applied semiannually (every 6 mo), group 3 had 38% SDF appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
196
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(220 citation statements)
references
References 22 publications
5
196
0
19
Order By: Relevance
“…The active caries treated with SDF usually turns into arrested caries, which is normally brown or black, hard, glossy, and non-progressive. SDF inhibits tooth demineralization and promotes remineralization [21,22]. However, this study did not alter the child eating habit which might affect the caries development.…”
Section: Discussionmentioning
confidence: 85%
“…The active caries treated with SDF usually turns into arrested caries, which is normally brown or black, hard, glossy, and non-progressive. SDF inhibits tooth demineralization and promotes remineralization [21,22]. However, this study did not alter the child eating habit which might affect the caries development.…”
Section: Discussionmentioning
confidence: 85%
“…Several trials have stressed that in their results, anterior teeth have much higher rates of arrest than posterior teeth 4145 As an example, one of the trials not included in the reviews, because it just published its 30-month results, 42 reports caries arrest by type of primary tooth using SDF 38% semiannually (Box 2). …”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
“…The difference in arrest rates in children receiving applications twice per year versus once per year was small between 24 and 30 months in all teeth, but among children who received annual application, those with visible plaque had a lesser likelihood of having their lesions arrested. Fung and colleagues 42 conclude that, for children with poor oral hygiene, caries arrest rate can be increased by increasing the frequency of application from annually to semiannually.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Eight studies 5,21,34-39 reported caries arrest with SDF application in children based on published literature in English for the last two decades ( Table 2). Five studies reported the use of 38% SDF for caries arrest 5,21,34,35,39 while three studies [36][37][38] reported 30% SDF. The researchers found that 38% of SDF application is most effective compared to a no treatment (negative control) or a placebo in the primary teeth for arresting dentine caries.…”
Section: Sdf In Caries Arrest Of Primary Dentitionmentioning
confidence: 99%